A Day for Sandcastles - Lawson, JonArno; Leng, Qin (Somerville, Massachusetts : Candlewick Press, 2022)
A ... wordless picture book celebrates creative problem- solving, teamwork, and the sun-splashed wonder of a day at the beach.
Keywords: Problem solving -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Sandcastles -- Juvenile fiction; Beaches -- Juvenile fiction; Problem solving -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Sandcastles -- Fiction; Beaches -- Fiction; Picture books